Competition and Pay Inequality Within and Between Firms - Gartenberg, Claudine; Wulf, Julie (Management Science, 2020)
How does market competition affect pay inequality between and within firms? Using division managers as a pool of similar workers and the Canada–U.S. Free Trade Agreement, we find that greater competition increases overall pay inequality between, but not within, firms. This null effect within firms is not driven by a lack of statistical power. Instead, we find that it arises primarily within subsamples of firms with higher predicted levels of social comparison. Increased competition leads to greater pay-performance sensitivity among the higher-paid managers within firms, while it leads to greater overpayment among the other managers. These patterns are consistent with firm principals offering higher-powered incentives to their best managers and overpaying the rest. Altogether, this study suggests that, while competition leads to greater pay inequality overall, principals aim to maintain equality within firms and do so through the differential provision of incentives among employees. This paper was accepted by Bruno Cassiman, business strategy.